Bioinformatics analysis and purification of beta glucosidase from anoxybacillus species - Kow, Pek Yee, 1990- author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - Universiti Teknologi Malaysia, 2014